Microwave-assisted fabrication and optimization of nickel cobalt phosphate for high-performance electrochromic supercapacitors - Mustafa, Muhammad Norhaffis; Mohd Abdah, Muhammad Amirul Aizat; Numan, Arshid; Sulaiman, Yusran; Walvekar, Rashmi; Khalid, Mohammad (Elsevier BV, 2023)
This study uses response surface methodology and central composite design (RSM/CCD) to explore the optimization of nickel cobalt phosphate (NiCoPO4) composites as effective materials for electrodes in electrochromic supercapacitors. The synthesis of NiCoPO4 powder is achieved through microwave-assisted techniques, and spin coating is employed to fabricate the NiCoPO4 composite electrode. Two factors, namely spin speed and time, are simultaneously investigated to assess their impact on the specific capacity of NiCoPO4 composites. Statistical analysis using Design Expert software indicates a quadratic model with a residual standard error of less than 4 . The NiCoPO4 composites are subjected to various characterization techniques, including FTIR, Raman, XRD, XPS, and FESEM with EDX. Additionally, comprehensive electrochromic energy storage performance analyses are conducted, encompassing EIS, CV, GCD, stability, optical, and kinetic studies. The NiCoPO4 electrode material exhibits distinct color changes, appearing black at 0.5 V and pale green at 0 V, which signify its electrochromic properties. Furthermore, NiCoPO4 electrode material demonstrates exceptional optical performance, with a specific capacitance of 48.95 cm2/C, and supercapacitive performance, with a specific capacity of 262.8C/g, thus highlighting the as-prepared NiCoPO4 potential as a promising electrode material for electrochromic supercapacitors.